(untitled) (Research, Society and Development, 2024)
Biographical research is a methodological approach that aims to investigate and understand an individual’s life in a deep and holistic way. This approach goes beyond chronological facts and external events, seeking to penetrate the most intimate layers of a person’s experience. By delving into personal narratives, memories and accounts, biographical research seeks to capture the unique complexity of a life, considering cultural, social and psychological influences. In this way, the Biographical Methodological Approach will be discussed, based on the studies of Marie-Christine Josso, with the purpose of contextualizing the research device created, entitled “Deck of Social Imaginary Meanings”. The aim is to publicize the possibility of creating research devices for the area of education and promoting the discussion of topics such as gender and diversity in teacher training. Reflecting on the intertwining of Biographical research and the investigative paths of research in Education.